Utilization of palm oil sludge in poultry diet. 4. Inclusion of fresh or dried fermented palm oil sludge in native chickens diet - Sinurat, A.P; Purwadaria, T; Pasaribu, T; Darma, J; Bintang, I.A.K; Togatorop, M.H (Indonesian Journal of Animal and Veterinary Sciences, 2001)
Fermentation processes increase the protein of palm oil sludge and produce some useful enzymes. However, drying process, especially with heating often affects the nutritive values of feed ingredients and the enzymes activity. Therefore, this experiment was designed to study the responses of native chickens when fed ration containing fresh or dried fermented palm oil sludge (FPOS). Experimental diets with different levels of fresh or dried FPOS (5, 10 and 15% equal to dried FPOS) were formulated with similar nutrient contents. A control diet with no FPOS was also included. Each treatment was replicated 5 times for 12 weeks. Performances (body weight, feed consumption, feed conversion and mortality) of chickens were recorded. Carcass yield, abdominal fat content, weight of liver and gizzard were measured at the end of feeding trial. Data were subjected to analysis of variance and different between means were tested by orthogonal procedures. Results during the starting period showed that, chickens fed FPOS diet gain more weight significantly than the control birds (298.1 vs. 264.7). The dry matter intake of the dry FPOS diet was significantly better than the fresh FPOS diet (2.88 vs. 3.32). The FPOS dietary levels did not affect body weight gain and dry matter intake of native chickens, significantly. However, increasing the FPOS levels worsen the dry matter conversion (DCR) significantly. Data during 12 weeks trial showed mat the body weight gain was not significantly affected by treatments. The dry matter intake of the FPOS diets were significantly higher than the control diet (3469 vs. 3065 g/bird), hence the DCR of the control diet was significantly better than the FPOS diets (3.28 vs. 3.62). Feeding dry FPOS resulted in a better DCR as compared to fresh FPOS (3.48 vs. 3.76), but not affected the dry matter intake. The FPOS dietary levels did not affect body weight gain and dry matter intake of native chickens, significantly. However, inclusion of 5% FPOS in me diet gave better DCR significantly, as compared with 15% FPOS (3.51 vs. 3.83). Feeding dry or fresh FPOS (5 - 15%) did not significantly affect the mortality, carcass yield, abdominal fat levels, weight of liver and weight of gizzard of native chickens. It is concluded that dry FPOS was better than the fresh FPOS and could be included in me native chickens diet up to 10%. Â  Key words: Palm oil sludge, fermentation, native chickens